1996
DOI: 10.1090/s0025-5718-96-00708-9
|View full text |Cite
|
Sign up to set email alerts
|

Computing all power integral bases in orders of totally real cyclic sextic number fields

Abstract: Abstract. An algorithm is given for determining all power integral bases in orders of totally real cyclic sextic number fields. The orders considered are in most cases the maximal orders of the fields. The corresponding index form equation is reduced to a relative Thue equation of degree 3 over the quadratic subfield and to some inhomogeneous Thue equations of degree 3 over the rationals. At the end of the paper, numerical examples are given.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

1996
1996
2005
2005

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…It is known, however, that there are no additional generators of any form for p ^ 13. Specifically, Gaal and Schulte [5] computed all power integral bases for a large collection of cubic fields, including the real cyclotomic field for p = 7; Gaal and Pohst [4] consider a family of totally real cyclic quintic fields and showed that only one, namely the real cyclotomic field for p = 11, admits a power integral basis, and they compute all the generators for this field; Gaal [2] computed all power integral bases for the first five totally real cyclic sextic number fields, which includes the real cyclotomic field for p = 13. In the work of Gaal, Pohst, and Schulte the generators are presented in a different form than in our work, but a close examination shows that we found all the generators for p ^ 13.…”
Section: Now G(x)mentioning
confidence: 99%
“…It is known, however, that there are no additional generators of any form for p ^ 13. Specifically, Gaal and Schulte [5] computed all power integral bases for a large collection of cubic fields, including the real cyclotomic field for p = 7; Gaal and Pohst [4] consider a family of totally real cyclic quintic fields and showed that only one, namely the real cyclotomic field for p = 11, admits a power integral basis, and they compute all the generators for this field; Gaal [2] computed all power integral bases for the first five totally real cyclic sextic number fields, which includes the real cyclotomic field for p = 13. In the work of Gaal, Pohst, and Schulte the generators are presented in a different form than in our work, but a close examination shows that we found all the generators for p ^ 13.…”
Section: Now G(x)mentioning
confidence: 99%
“…In several cases (see, e.g., [9], [10], [11], [12], [13]), this problem was reduced to relative Thue equations.…”
Section: István Gaál and Michael Pohstmentioning
confidence: 99%
“…e.g. [3] for the basic ideas of the algorithm) we solved the unit equation (9) corresponding to the index form equation (5). The solutions allow to express ε/ε and hence also ε, which gives (x 2 , x 3 , x 4 , x 5 ) in view of (8), by taking conjugates and solving the corresponding system of linear equations.…”
Section: Lemmamentioning
confidence: 99%
“…e.g. [6], [4], [3], [5]). For number fields of higher degree k the problem becomes difficult because of the large degree k(k − 1)/2 of the index form equation and the number of variables k − 1.…”
Section: Introductionmentioning
confidence: 99%